TINJAUAN HUKUM TERKAIT KAMPANYE PILKADA DITENGAH PANDEMI COVID-19 - Husnulwati, Sri (Solusi, 2021)
The Government of the Republic of Indonesia has decided to continue the implementation of the Regional Election (pilkada) for governor and deputy governor, regent, and deputy regent, the mayor and deputy mayor process simultaneously in the Covid-19 Pandemic has generated many counter attitudes from various circles. This purpose of this is to review the legal related to the regulatory readiness, especially the simultaneous regional election campaign in the Covid-19 pandemic. The research method used in this research is the legal normative method. The results of this research are, (a) The process of implementing the campaign by the health protocol regulated through PKPU Number 13 of 2020 Article 57, Article 63 and Article 58 paragraph (1) and (2), (b) The campaign materials, it is regulated through PKPU Number 10 of 2020 Article 60 paragraph (2) and (3) PKPU Number 13 of 2020 Article 62, and (c) prohibited activities and sanctions are regulated through PKPU Number 13 of 2020 Article 88B, 88C paragraph (1) and paragraph (2).